2021
DOI: 10.3389/fevo.2021.640121
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Species in Puerto Rico: The View From El Yunque

Abstract: Native flora and fauna of Puerto Rico have a long biogeographic connection to South America. Theory and empirical evidence suggest that islands, particularly those distantly isolated from the mainland, should be more susceptible to naturalizations and invasions of non-native species than continental areas. Anthropogenic disturbances can facilitate accidental and deliberate introductions of non-native species. In this study, we asked: What is the current status of introduced species within El Yunque National Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Additionally, it has been suggested that native species cope better with hurricane disturbances and have higher survival rates than non-native species (Brokaw et al 2012;Duryea et al 2007;Duryea and Kampf 2014). These differences in the responses of native and non-native species to hurricane damage could explain (at least in part) the high mortality rates observed in our yards that are dominated by non-natives and the relative lower mortality rates reported for natural forests, which are areas often dominated by native species or with lower proportion of non-native species than our yards (Ackerman et al 2017;Zimmerman et al 2021). However, more studies evaluating hurricane responses of native and non-native species in urban and natural forests are needed to understand the extent of these results.…”
Section: Hurricane-driven Changes In Vegetation Structure and Compositionmentioning
confidence: 78%
“…Additionally, it has been suggested that native species cope better with hurricane disturbances and have higher survival rates than non-native species (Brokaw et al 2012;Duryea et al 2007;Duryea and Kampf 2014). These differences in the responses of native and non-native species to hurricane damage could explain (at least in part) the high mortality rates observed in our yards that are dominated by non-natives and the relative lower mortality rates reported for natural forests, which are areas often dominated by native species or with lower proportion of non-native species than our yards (Ackerman et al 2017;Zimmerman et al 2021). However, more studies evaluating hurricane responses of native and non-native species in urban and natural forests are needed to understand the extent of these results.…”
Section: Hurricane-driven Changes In Vegetation Structure and Compositionmentioning
confidence: 78%
“…These consequences may have profound impacts on the future of natural forests by altering successional regeneration and productivity, as well as the vulnerability, resilience, and capacity of the biota to adapt to climate change and altered disturbance regimes in which large‐scale, extreme events such as drought, tropical storms, and hurricanes are increasing. While well‐conserved tropical forests may be resistant to invasions by vascular plants (e.g., Ackerman et al, 2017; Zimmerman et al, 2021), we and others have shown that anthropogenically disturbed tropical forests can be quite vulnerable to biological invasions (Asner et al, 2008; Bempah et al, 2021; Rothstein et al, 2004) and that invasive alien species have the potential to severely alter the composition of tropical forests across different successional stages and have a long‐term impact on the abundance and richness of native species.…”
Section: Discussionmentioning
confidence: 99%
“…Black rats and house mice are two rodent species that occupy the Luquillo Experimental Forest (LEF) of northeastern Puerto Rico (Shiels & Ramírez de Arellano, 2018; Zimmerman et al, 2021). There are no extant native rodents in Puerto Rico, and the ecological roles of the three or more native rodent species that were in Puerto Rico's prehistoric fauna are largely unknown (Turvey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%